Role and interaction of bacterial sphingolipids in human health - Bai, Xiaoye; Ya, Ru; Tang, Xiaoyu; Cai, Mingwei (Frontiers in Microbiology, 2023)
Sphingolipids, present in both higher animals and prokaryotes, involving in cell differentiation, pathogenesis and apoptosis in human physiological health. With increasing attention on the gut microbiome and its impact on well-being, there is a renewed focus on exploring bacterial sphingolipids. This review aims to consolidate the current understanding of bacterial sphingolipids and their impact on host health.Compared to mammalian sphingolipids, bacterial sphingolipids are characterized by odd chain lengths due to the presence of branched alkyl chains. Additionally, intestinal microbial sphingolipids can migrate from the gut to various host organs, affecting the immune system and metabolism. Furthermore, the intricate interplay between dietary sphingolipids and the gut microbiota is explored, shedding light on their complex relationship. Despite limited knowledge in this area, this review aims to raise awareness about the importance of bacterial sphingolipids and further our understanding of more uncharacterized bacterial sphingolipids and their significant role in maintaining host health.